Biometric attendance system using NodeMCU platforms - Ali, Rozita Binti Md (Indonesian Institute for Counseling, Education, and Therapy (IICET), 2022)
The purpose of this study is to design a Biometric Attendance System that will provide lecturer and academic advisor administrators with tools for managing student attendance as well as regular users such as students. This system manages student attendance by storing student information, course information, and student attendance records at Politeknik Kuala Terengganu. The system consists of two main components : a hardware component and a web-based component. This system development model is intended to be used to design web-based systems by utilising the AGILE Model as a model of the system development life cycle. Additionally, to connect the system to the network, Network Design Diagrams are employed. Visual Basic was utilised to construct this system, while MYSQL was used to store student attendance data. Additionally, the functional framework for this system includes a Node MCU ESP8266 Wi-Fi Module, an R307 fingerprint sensor, a 0.96